Pengembangan Perangkat Pembelajaran Berbasis Deep Learning untuk Pembelajaran Keberagaman Budaya di Sekolah Dasar - Eva Yuliawati; Abdul Fatah; Haryono (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and examine the effectiveness of deep learning-based instructional tools, consisting of a teaching module and Google Sites-based learning media, in improving elementary school students’ conceptual understanding of cultural diversity. The study employed a Research and Development (R&D) method using the ADDIE model and was conducted with 34 fourth-grade students at SDN Gerendong 2, Banten, Indonesia. Data were collected through validation sheets, observations, and learning outcome tests and were analyzed using descriptive statistics and paired-sample t-tests. The results showed that the developed instructional tools were highly valid, with Aiken’s V coefficients ranging from 0.88 to 0.94 and validation percentages exceeding 90% across the material, media, and language aspects. The paired-sample t-test results indicated a significant difference between the pretest and posttest scores (p < 0.001), with an average N-gain score of 0.63, which falls into the moderate category, and a very large effect size (Cohen’s d = 4.02). These findings demonstrate that the instructional tools effectively improved students’ conceptual understanding. Furthermore, the results indicate that deep learning-based instructional tools integrated with digital media can enhance meaningful and student-centered learning. This study contributes to the growing body of knowledge on instructional design by providing empirical evidence regarding the effectiveness of combining teaching modules and web-based media. It also offers practical implications for teachers in implementing innovative learning strategies that promote conceptual understanding in elementary education.